2015
DOI: 10.1007/s10495-015-1204-3
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones improve cardiac function and decrease expression of pro-apoptotic proteins in the heart of rats 14 days after infarction

Abstract: Apoptosis is a key process associated with pathological cardiac remodelling in early-phase post-myocardial infarction. In this context, several studies have demonstrated an anti-apoptotic effect of thyroid hormones (TH). The aim of this study was to evaluate the effects of TH on the expression of proteins associated with the apoptotic process 14 days after infarction. Male Wistar rats (300-350 g) (n = 8/group) were divided into four groups: Sham-operated (SHAM), infarcted (AMI), sham-operated + TH (SHAMT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
1
16
0
3
Order By: Relevance
“…T3 supplementation was associated to the reversal of this expression signature. These findings extend and integrate previous data showing a protective role of TH against cardiomyocyte apoptosis and against the activation of p38/Mapk/Jnk signaling and pro-fibrotic cascade following heart ischemia 15 , 16 , 24 , 25 . In addition, we found that several transcripts of non-cardiomyocyte origin, implicated in inflammation and cell adhesion processes, were also modulated by T3 indicating that several different myocardial cell types may be involved in the protective effects of TH (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…T3 supplementation was associated to the reversal of this expression signature. These findings extend and integrate previous data showing a protective role of TH against cardiomyocyte apoptosis and against the activation of p38/Mapk/Jnk signaling and pro-fibrotic cascade following heart ischemia 15 , 16 , 24 , 25 . In addition, we found that several transcripts of non-cardiomyocyte origin, implicated in inflammation and cell adhesion processes, were also modulated by T3 indicating that several different myocardial cell types may be involved in the protective effects of TH (see Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The doses of T3, as well as the time interval between drug injection and AlP intoxication (30 min) were chosen according to literature review [16,24,32].…”
Section: Experimental Designmentioning
confidence: 99%
“…Several possible mechanisms have been proposed for antinecrotic and antiapoptotic effects of T3 administration, such as decreasing NF-ϰB, P53, BAX, BCL-2, activation of phosphatidylinositol 3' kinase/protein kinase B (PI3K/Akt) and extracellular regulated kinase 1 and 2 (ERK1/2) signaling [11,39]. On the other hand, in vivo studies demonstrated that T3 can ameliorate acute myocardial infarction through decreasing ROS and increasing total antioxidant capacity and GPx in myocardial tissue [16]. In the light of flow cytometric assay, it is ascertained that cellular apoptosis is the main…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In relation to lung congestion, neither of the parameters evaluated (lung weight and lung/tibial length) showed any difference between the groups. This result indicates that the animals did not present this characteristic of heart failure (de Castro et al., 2016), despite cardiac dilatation and an increase in cardiac wall stress. In view of that, it was not possible to evaluate the effect of the interventions for this parameter.…”
Section: Discussionmentioning
confidence: 83%
“…Recent research has brought to light the possible benefits of thyroid hormone treatments (T3 and T4) on LV remodelling after MI (de Castro et al., 2016; Mourouzis et al., 2013; Pantos et al., 2007). It seems that low doses of thyroid hormones are able to provide benefits without adverse effects (Rajagopalan et al., 2016; Rajagopalan et al., 2017; Teixeira et al., 2017); in addition, thyroid hormones exert both organ‐targeted and systemic effects (Razvi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%